RELATIONSHIP BETWEEN OBESITY ANDPHYSICAL ACTIVITY IN CHILDREN - Nimra Mustafa et al (Baqai Journal of Health Sciences)
Background: Physical activity (PA) plays an important role in prevention of obesity in children and adolescents. Current evidence provides useful visions to better understand how they just rely on each other. The aim of this study was to determine the relationships between obesity and PA in children. Material & Methods: This study was conducted on 100 children, fourth to eight class, and aged between 9- 14 years. Body Mass Index and PA were measured in 49 females and 51 males. Physical activity was measured using the Physical Activity Questionnaire for Children and for BMI, height was measured by inch tape and weight was measured by weight machine. Pearson’s correlation co-efficient was used to determine the correlation between PA and obesity. Results: This study showed that out of 100 participants only 12 were participated in low physical active. Mostly children 45 participate in low-moderate level of physical activity, 32 children participated in moderate, 11 were high-moderate and 0% participated in high level of physical activity on a weekly basis and BMI interpretation was only 9 were underweight, 53 were normal, 7 were overweight, 31 were obese. Results showed a moderate negative correlation between BMI and physical activity (r = -0.3325, P =0.3173). Conclusion: It has become a combined social responsibility of parents, caregivers, educators and health professionals to aware children about the negative effects of obesity and helps them in implementing strategies to prevent its development.